Case report: MRI changes of the inner ear in an MD patient with suspected immune dysfunction - Chen, Yurun; Zhao, Pengfei; Ma, Xin; Diao, Tongxiang; Yu, Lisheng (Frontiers in Neurology, 2023)
Objectives: The primary objective of this study was to present the progressive changes from labyrinthitis to endolymphatic hydrops (EH) demonstrated in the inner ear MRI of a patient with MD and suspected immune dysfunction.Patient: This 31-year-old male was diagnosed with MD and suspected autoimmune diseases.Interventions: Immunosuppressants and biological agents.Results: Changes in the patient's progress revealed that inner ear immune and inflammatory changes might induce EH, which may eventually turn into MD.Conclusions: This case is the first documented case of MRI revealing progressive changes from inflammatory response to endolymphatic hydrops in the inner ear. It shows the correlation between MD and inflammation visually. It is of great significance to reveal the pathogenesis of MD to further assist in the guidance of treatment decision making.